Hubungan Perilaku Menguras, Menutup, Mengubur Plus dengan Kejadian Demam Berdarah Dengue pada Balita di Kelurahan Kalibaru - Claudia Silfi Amanda; Dameria Br Saragih; Ernawati Ernawati (Pustaka Galeri Mandiri, 2026)
Dengue Hemmorhagic fever (DHF) is still a disease that often becomes a public health polemic in Indonesia, especially in children under five. One of the recommended prevention efforts is the Menguras, Menutup, Mengubur Plus behavior. However, public awareness in implementing 3M Plus is still low. Objective: To understand the relationship between 3M Plus behavior and the incidence of DHF in children under five in Kalibaru Village, North Jakarta. This study adopted descriptive quantitative with cross-sectional approach. The population of this study was mothers with toddlers with a sample random sampling technique of 99 respondents. The instrument used 3M Plus questionnaire and DHF questionnaire and analyzed through the use of Chi-square test. The findings elaborated that 66.7% of respondents complied with 3M Plus and 23.2% of toddlers experienced DHF in the past year. The findings suggest that there is a significant relationship between 3M Plus and the incidence of DHF in children under five with a P Value: 0.040. This indicates that 3M Plus has an effect on the incidence of DHF in toddlers. Conclusion: The more obedient parents are in implementing 3M Plus, the smaller the risk of toddlers being infected with DHF disease